ASRAR DIGITAL TRANSACTIONS: AN INTERNATIONAL LEGAL REVIEW OF GLOBAL E-COMMERCE - Artia Nabila Mayangsari; Rina Arum Prastyanti (Adisam Publisher, 2025)
E-commerce has fundamentally transformed global transactional practices, enabling seamless cross-border exchanges. However, within the framework of international trade, legal complexities arise when transactions involve jurisdictions with diverse legal systems. This study critically examines the international legal dimensions of global e-commerce, focusing on issues of jurisdiction, consumer protection, data security, and dispute resolution. Employing a normative juridical method and literature-based analysis, the research highlights the urgent need for regulatory harmonization and cross-national cooperation to build a fair, coherent, and globally applicable legal framework. The findings underscore the importance of strengthening international agreements and establishing effective mechanisms for digital dispute resolution. It is concluded that international law must adapt continuously to the evolving landscape of digital commerce and technological innovation.